The effects of self-disclaimer Instagram captions on young women's mood and body image: The moderating effect of participants' own photo manipulation practices. (September 2021) - McComb, Sarah E.; Gobin, Keisha C.; Mills, Jennifer S.
Highlights: Exposure to thin-ideal Instagram images caused lowered mood and body satisfaction. Self-disclaimer captions did not protect young women's mood or body image. Type of self-disclaimer had no effect on mood or body image. Specific self-disclaimers reduced body comparison intent among frequent photo editors. Abstract: The current experiment investigated the impact of attaching self-disclaimer captions (i.e., captions about whether photos had been edited) to thin-ideal Instagram photos on young women's body image and mood. Participants were 311 undergraduate students aged 18–25 years. Participants were randomly assigned to view images of a thin woman on Instagram with no captions, or with a generic, specific, or warning self-disclaimer caption, and completed pre and post measures of body image and mood and a questionnaire about their own photo-editing practices. Across all conditions, exposure to the images resulted in decreased body satisfaction, likelihood to compare one's body to another's, happiness, confidence, and anxiety. There was no significant effect of disclaimer type on body image or mood, and therefore no type of self-disclaimer had an ameliorating effect. However, specific disclaimers were superior to the other disclaimers at reducing likelihood to compare one's body to another's, for women high on photo manipulation. Future research should be conducted in adolescent girls and men.